Social Action in the Brunca Region, a view from the South Campus and the former Golfito Campus, University of Costa Rica. Period 2006-2022 - Hidalgo Redondo, Giselle (2023)
This paper is oriented to visualize the scope in the Brunca Region of social action projects registered in the South Headquarters and the former Golfito Campus, both academic units of the University of Costa Rica, during a period of 16 years. The main objective of this inquiry is focused on knowing the growth of the projects per year, type of project modality in Teaching Extension, Cultural Extension, and University Community Work, the Student Initiatives, the location by county, the topics addressed, academic degree and employment status of teachers, and the College Extension Committee. Therefore, the projects registered as active, inactive, and closed condition from 2006 to 2022 are analyzed; the information from the institutional digital platform (Bitè) will be used because it stores the academic and budgetary information of the Vice Chancellor for college extension.